FIKIH DI PESANTREN SALAF (Strategi Pengembangan Fikih Salaf di Pesantren Hidayatul Mubtadi’in Lirboyo Kediri) - Zaenul Mahmudi (lp2m-uin malang, 2008)
In the course of Indonesian history, pesantren has had significant and strategic role, both in grabbing, defending, and filling in it’s independence. In modern day, pesantren still become reference for people to make their problem, especially legal problems tobe solved. The aims of this research are to looking for the base for developing fiqh and it’s development strategy. This research use qualitative method and social definition paradigm to comprehend the religious leaders (kiai) and religious students (santri) idea in Pesantren Hidayatul Mubtadi’in Lirboyo Kediri. The results of this research show that the base of pesantren development in fikh discipline is traditionalism or orthodox (salaf) label on the pesantren and the strategies in fikh development are to a) looking after the orthodox ulama thoughts, b) countering modern thoughts that criticize the orthodox ulama thoughts, c) actualizing orthodox fiqh thoughts by optimalizing rules of fiqh (qawâid al-fiqhiyyah) and turning on book writing as alternative solution for actual problems in society.Keywords: Fiqh, Religious Leader, Religious Student